Fat Grafting and Adipose-Derived Regenerative Cells in Burn Wound Healing and Scarring: A Systematic Review of the Literature - Condé-Green, Alexandra; Marano, Andrew A; Lee, Edward S; Reisler, Tom; Price, Leigh Ann; Milner, Stephen M; Granick, Mark S (Plastic and reconstructive surgery (1963), 2016)
There is an abundance of literature supporting the efficacy of fat grafting in aesthetic and reconstructive cases. There has been a recent emphasis on the regenerative capacity of adipose-derived stem cells and their utility in the improvement of wound healing and scarring provided by their cytokine and growth factor profiles. Despite the wealth of evidence supporting their efficacy, little attention has been paid to their utility in burn treatment. The authors' purpose was to provide an analysis of the literature regarding the use of fat grafting and regenerative cells in the treatment of burn wounds to guide surgeons and scientists on their clinical use. A systematic review of the literature was performed by a thorough search of 12 terms using the PubMed, Medline, and Cochrane databases. Two hundred forty-one articles were subject to evaluation by predetermined inclusion and exclusion criteria. Six murine and 12 human studies were selected, including case-control studies, case series, and case reports. They describe histologic and clinical effects of fat grafting and regenerative cell therapy, including improvements in burn scar size and texture, enhanced angiogenesis, decreased inflammation, alleviation of pain, and return of function. There is a dearth of randomized controlled trials and quantitative analysis supporting the efficacy of fat grafting and adipose regenerative cells in burns. However, the subjective improvements in scars are encouraging. The authors hope that this review will be a foundation for future studies and will highlight the breadth of knowledge yet to be explored by this therapy. Therapeutic, IV.